2019
DOI: 10.1103/physrevmaterials.3.125604
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity and thermal transport of commodity plastics

Abstract: Applications of commodity polymers are often hindered by their low thermal conductivity. In these systems, going from the standard polymers dictated by weak van der Waals interactions to biocompatible hydrogen bonded smart polymers, the thermal transport coefficient κ varies between 0.1 − 0.4 Wm −1 K −1 . Combining all-atom molecular dynamics simulations with some experiments, we study thermal transport and its link to the elastic response of (standard and smart) commodity plastics. We find that there exists a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 58 publications
2
37
0
Order By: Relevance
“…As expected from the blending of two materials, κ with x PLA shows a monotonic variation between the κ values of a pure PLA and a pure PMMA systems. While κ values are known for the pure phases on PMMA and PLA, which is also consistent with the earlier experiments [44,45] and simulations [32], we report κ data for PMMA-PLA blends here. This shows an internal correlation between the linear elasticity, mechanics, and thermal transport of commodity polymer blends.…”
Section: Mechanical Response and Thermal Transportsupporting
confidence: 92%
See 3 more Smart Citations
“…As expected from the blending of two materials, κ with x PLA shows a monotonic variation between the κ values of a pure PLA and a pure PMMA systems. While κ values are known for the pure phases on PMMA and PLA, which is also consistent with the earlier experiments [44,45] and simulations [32], we report κ data for PMMA-PLA blends here. This shows an internal correlation between the linear elasticity, mechanics, and thermal transport of commodity polymer blends.…”
Section: Mechanical Response and Thermal Transportsupporting
confidence: 92%
“…1 atom OPLS force field is used to model PLA [30], while we have used a set of modified OPLS parameters for PMMA [31]. Earlier it has been shown that the PMMA force field parameters reasonably capture the properties of the solid, solvent-free PMMA, such as the specific volume, the macroscopic elastic moduli, and the thermal transport coefficient [32]. In this work, we have also validated that the PLA parameters give the correct estimates of specific volume at temperature of T = 300 K (i.e., 8.06×10 −4 m 3 /kg for experiments and 8.11×10 −4 m 3 /kg for simulations), elastic modulus, and thermal properties.…”
Section: B All Atom Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also developed a theoretical model related to bond energy, backbone rotation, in-plane bond ratio, and atomic amass to predict thermal conductivity of crystalline polymers [26]. Ruscher et al uncovered the link between elasticity and thermal conductivity of several polymers [27]. An et al investigated the effects of water content and cross-linking on the thermo-mechanical property of polyacrylamide hydrogels [28].…”
Section: Introductionmentioning
confidence: 99%